2011
DOI: 10.1111/j.1747-0285.2011.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Rottlerin Exhibits Antiangiogenic Effects In vitro

Abstract: Rottlerin, a natural product purified from Mallotus philippinensis, has a number of target molecules and biological effects. We recently found that Rottlerin caused growth arrest in MCF-7 breast cancer cells and human immortalized keratinocytes, through inhibition of NFκB and downregulation of cyclin D-1. To evaluate whether this effect could be generalized to primary cells, human microvascular endothelial cells were treated with Rottlerin. In this study, we demonstrated that Rottlerin prevents basal and TNFα-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Some studies showed that rottlerin inhibited cancer cell growth and induced apoptosis in a variety of human cancers [13, 14, 41, 42]. Moreover, rottlerin could suppress growth of human pancreatic tumors in nude mice [43, 44]. We also found that overexpression of Cdc20 enhanced glioma cell proliferation, whereas depletion of Cdc20 suppressed cell growth in glioma cells.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Some studies showed that rottlerin inhibited cancer cell growth and induced apoptosis in a variety of human cancers [13, 14, 41, 42]. Moreover, rottlerin could suppress growth of human pancreatic tumors in nude mice [43, 44]. We also found that overexpression of Cdc20 enhanced glioma cell proliferation, whereas depletion of Cdc20 suppressed cell growth in glioma cells.…”
Section: Discussionsupporting
confidence: 50%
“…Rottlerin was also exhibited its anti-angiogenesis function via inhibition of human microvascular endothelial cell proliferation and tube formation on Matrigel [31]. Moreover, rottlerin was reported to enhance IL-1β (interleukin-1β)-induced COX-2 (cyclooxygenase-2) expression via activation of p38 MAPK (mitogen-activated protein kinases) in breast cancer cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor NFκB, a key component for the expression of many cellular genes, has been implicated in the signaling pathways of several growth factors produced by platelets, controlling cytokine expression and regulating inflammatory response, with effects on corneal wound healing and angiogenesis [33]. Gene silencing of NFκB was shown to impair in vitro wound healing by keratinocytes [34]; moreover, natural products also used for wound healing, were able to exert potent antiproliferative and antiangiogenic activity by blocking the NFκB cascade in different cell types, including endothelial cells [35]. The interconnection of inflammation and angiogenesis was also demonstrated for substances able to reduce NFκB activation by VEGF and to inhibit the angiogenic cascade both in vitro and in vivo [36].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we found that Rottlerin, a natural polyphenol purified from the kamala powder [2], may act as an antitumor agent by a variety of mechanisms, such as Akt and ERK-independent cell cycle arrest in MCF-7 cells [3], functional suppression of the transcription factor NF κ B in MCF-7, HT-29 cells [4], and in HaCaT keratinocytes [5] and angiogenesis inhibition [6]. Several other studies have reported the anticancer potential of Rottlerin in different human malignant tumor cells.…”
Section: Introductionmentioning
confidence: 99%